2021
DOI: 10.21203/rs.3.rs-746606/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emergence of Extended-Spectrum β-Lactamase Producing and Hybrid Pathotypes of Escherichia Coli Isolates from Diarrheic Human Cases: A New Public Health Concern in Iran

Abstract: Background: Intra-intestinal pathogenic strains of Escherichia coli are responsible for mild to severe gastrointestinal lesions, which are mediated by various virulence factors. In this study, we have focused on a comprehensive set of E. coli pathotypes, including STEC, EPEC, EHEC, ETEC, and some hybrid pathotypes including, STEC/ ETEC, EHEC/ ETEC, and EPEC/ ETEC.Methods: Totally, 467 stool samples were obtained from gastrointestinal patients during four years (2016 to 2020). Four pathotypes of E. coli (EPEC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…All DEC Pathotypes categorized according to molecular contents of some virulence genes: eae and bfpA for EPEC [12]; st1a, st1b and ltb1 for ETEC; aggR for EAEC; stx1 and stx2 for EHEC/STEC; ipaH for EIEC; daaD for DAEC [13]. Many studies revealed that, the most prevalent diarrheagenic E. coli were ETEC, EPEC, EAEC, AIEC, EHEC/STEC and DAEC [14][15][16][17]. Concern phylogroups of EPEC, the results gathered from 18 studies for 433 EPEC isolates revealed that: B1 compile (39.3%), A(23.3%), B2(18.2%), D(8.5%), (6.2%, 3.5% and 0.9%) for E, C and F phylogroups respectively (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Diarrheagenic E Coli (Dec) Phylotypesmentioning
confidence: 99%
“…All DEC Pathotypes categorized according to molecular contents of some virulence genes: eae and bfpA for EPEC [12]; st1a, st1b and ltb1 for ETEC; aggR for EAEC; stx1 and stx2 for EHEC/STEC; ipaH for EIEC; daaD for DAEC [13]. Many studies revealed that, the most prevalent diarrheagenic E. coli were ETEC, EPEC, EAEC, AIEC, EHEC/STEC and DAEC [14][15][16][17]. Concern phylogroups of EPEC, the results gathered from 18 studies for 433 EPEC isolates revealed that: B1 compile (39.3%), A(23.3%), B2(18.2%), D(8.5%), (6.2%, 3.5% and 0.9%) for E, C and F phylogroups respectively (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Diarrheagenic E Coli (Dec) Phylotypesmentioning
confidence: 99%